Method development and validation for determination of pharmaceuticals and personal care products in river water and sewage - Tan, Eugenie Sin Sing (2012)
Pharmaceuticals and Personal Care Products (PPCPs) are classified as the new emerging class of pollutants by the United States Environmental Protection Agency (U.S. EPA) recently. Its ubiquitous nature coupled with its high persistency in the environment is alarming. Moreover, some PPCPs are endocrine disrupting compounds responsible for feminization of male fishes via production of viltellogenin. Occurrences of antibiotics in the environment induce high bacterial resistance. PPCPs were widely manufactured and administered in Malaysia but little or no quantification was carried out. Lack of data could be attributed to the absence of a recognized, comprehensive and conclusive method for PPCPs analysis. As such, this method aims to provide a robust and sensitive method for identification and quantification of PPCPs in river water, Sewage Treatment Plant (STPs) influent, intermittent and effluent. This method is specially formulated for simultaneous extraction, detection and quantification of multi-classes PPCPs in a 25 minutes run-time. This is a pioneering method for quantification of acetaminophen, sulfamethoxazole, diclofenac, atenolol, metoprolol, DEET and oxybenzone in Atmospheric Pressure Chemical Ionisation (APCI) mode. Method had been validated for high repeatability and reproducibility; Relative Standard Deviations (RSD) for both was less than 10%. Quantification of PPCPs is often a trace analysis; thus, a good sensitivity is needed. As such, Instrument Quantification Limits (IQLs) for PPCPs were in the range of 0.05-1.0 μg/L; meanwhile, Method Quantification Limits (MQLs) for ultrapure water were within 0.3-15 ng/L. In addition, Solid Phase Extraction (SPE) recoveries were above 75% for most PPCPS demonstrating good accuracy. Lower matrix suppression in APCI mode had enabled quantifying PPCPs in complex matrices producing lower baseline chromatograms and sharper peaks resolutions. Subsequently, the method was applied to investigate environmental occurrences of PPCPs. Twelve out of eighteen PPCPs were detected in river water samples. Five PPCPs were quantified above 1000 ng/L; they were caffeine, estradiol, estriol, estrone and naproxen. On the other hand, three sewage treatment plant (STPs) with different operational mechanisms were sampled. Natural hormones (estradiol, estriol, estrone and progesterone) and personal care products (caffeine, DEET and oxybenzone) constituted majority of influents. Highest detected in influent was caffeine whose mean concentration was 14858.4 ng/L. Thirteen PPCPs were detected in all STP effluents. Highest concentration in effluent was estriol whose mean concentration was 2160.6 ng/L. In a nutshell, PPCPs were not efficiently removed by Malaysian STPs. Thereafter, Environmental Risk Assessments (ERA) was used to evaluate possible aquatic toxicities in Langat River. High risks of acute toxicities were found for naproxen and sulfamethoxazole. Several PPCPs exhibited high chronic toxicities namely diclofenac, estradiol, ethynylestradiol, estriol, estrone, and sulfamethoxazole. Naproxen exhibited medium risk. Metoprolol and DEET exhibited low chronic risk. Immediate reduction measures were demanded for four steroid hormones; they were estradiol, estriol, estrone and ethynylestradiol.